Efektifitas Umpan Tiruan yang Berbeda Warna Terhadap Hasil Tangkap Ikan tongkol (Euthynnus sp) di Perairan Tenggara Karangsem Bali - Putra, I Kadek Dedy Antara; Karang, I Wayan Gede Astawa; Faiqoh, Elok; As-syakur, Abd. Rahman (Journal of Marine and Aquatic Sciences, 2020)
Catching Tuna Fish ( Euthynnus sp.) in territorial waters of Southeast Karangasem, Antiga Kelod Village using trolling is very influenced by the type of baited. In a manner line, there are two type of baited that used for trolling, fishworm and lure. The objective of this research is to determine the effectiveness and the effect of lure on tuna fish catch ( Euthynnus sp.) In territorial waters of Southeast Karangasem, Antiga Kelod Village. All of three baits are made about the size of the baits and have the same color, there are blue-white, red-white, and green-white, and it’s operated simultaneously on one unit trolling line for 12 times . This research using descriptive comparative analysis and complete randomized design statistic analysis (RAL). The results of this research obtain, the blue-wait color of the bait can produce 146 tuna fish ( Euthynnus sp.) with an effectiveness value 34.27%, with average value of results catch is 12 tails on once trip. While for red-white color, produce 220 tuna fish with an effectiveness value 51.64%, and the average value of results catch is 18 tails on once trip, and the produce of green-white color is 60 tuna fish with effectiveness value 14.08%, the average outcome catch 5 tails on once trip.  Based on the results of the research The red-white bait was a bait with the highest catch and the highest effectiveness value.